On the Primitive Dwellings and Hypogea of the outer Hebrides (Proceedings of the Society of Antiquaries of Scotland, 1867)
The author describes various styles of domestic building used across the Hebrides, St Kilda and the west coast of the Scottish mainland. He does so with the intention of analysing which features may be traced back to earlier styles of architecture used in the area. He is particularly interested in dwellings that are partially underground.These buildings are then compared to accounts of structures in similarly cold, damp climates where the inhabitants may have had difficulty accessing wood as a construction material. In the final part of the article the author speculates about the purpose, builders and age of the sites he has described.